Audit Evidence Sufficiency and Its Role in Auditor Opinion Formation (gjstudies, 2024)
This research presents a novel, cross-disciplinary framework for conceptualizing and quantifying audit evidence sufficiency, moving beyond traditional binaryor threshold-based models. Drawing inspiration from quantum-inspired probability frameworks and information theory, we propose that evidence sufficiency is notmerely a matter of volume but of contextual coherence, informational density, andthe resolution of cognitive dissonance within the auditor’s mental model. Traditional auditing standards provide qualitative guidance on sufficiency, yet they lacka rigorous, quantifiable methodology for determining when evidence is ’enough’ tosupport an opinion. Our methodology integrates concepts from Dempster-Shafertheory of evidence to handle uncertainty and conflicting information, alongside acognitive load model adapted from human-computer interaction research to assessthe point at which additional evidence ceases to materially reduce auditor uncertainty. We formulate the problem as one of optimizing an ’evidential confidencefunction’ rather than accumulating checkmarks. Through a simulated audit environment involving complex, multi-source transactional data—inspired by challengesin domains like Anti-Money Laundering (AML) systems—we demonstrate that ourframework leads to more consistent opinion formation under conditions of information ambiguity compared to traditional heuristic approaches. Results indicatea 22% reduction in opinion divergence among auditors in high-ambiguity scenariosand a more robust linkage between the nature of evidence and the type of auditopinion rendered. The study’s originality lies in its rejection of the additive evidenceparadigm, instead positing sufficiency as a state of cognitive equilibrium achievedthrough structured reasoning with imperfect and often contradictory data. Thisre-conceptualization has significant implications for audit efficiency, the development of next-generation audit support systems, and the theoretical understandingof professional judgment in assurance services